Evaluation of retrospective analysis of surgical treatment of inflammatory and dystrophic periodontal lesions according to the data of the Department of Dental Surgery at the Tashkent State Dental Institute - Gaybullaev, ElbekAzizbekovich (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses data on the retrospective analysis of surgical treatment of inflammatory and dystrophic periodontal lesions and the reasons for patients refusing medical treatment within the period from 2009 to 2019, conducted at the Department of Surgical Dentistry of Tashkent State Dental Institute (TSDI). It has been proved that the most frequent common factors causing periodontitis are gastrointestinal diseases, and site related factors should include tooth malposition. Negative experience in medical history is proved prevailing reason for patients refusing surgical treatment using promising techniques, as many patients are aware of the increased teeth sensitivity and dental cervix exposure after the procedure. These are the reasons whythis problem remains urgent today.